Cooperation and social justice - Heath, Joseph, 1967- (University of Toronto Press, 2022)
"It is a common approach in contemporary political philosophy to view society as a system of mutually beneficial cooperation. This cooperation is difficult to achieve, often requiring a great deal of bargaining and compromise. Agreement is facilitated by principles of social justice, which determine the terms of reasonable compromise. And yet the application of these principles is also constrained by the scope of the cooperative system, which results in outcomes that often fall short of our ideals. Cooperation and Social Justice explores a set of issues that arise in this uncomfortable region, lying between our utopian ideals and the pragmatic constraints imposed by society. In six previously unpublished essays, philosopher and award-winning author Joseph Heath explores the connection between principles of justice and the institutional arrangements required to achieve them. Topics include the feasibility of socialism, objections to profit under capitalism, the significance of status inequality, the question of open borders and immigration, the stigmatization of self-control failure, and debates over racial inequality in the United States. Ultimately, Cooperation and Social Justice reveals that one cannot think about questions of social justice without also taking seriously the institutional arrangements through which they may or may not be realized."--